Аналіз основних складових чинників впливу на соціальну ринкову економіку країни - Абашина, О. В.; Abashina, О. (КНТУ, 2013)
Приведено результати аналізу основних складових чинників впливу на соціально орієнтовану ринкову економіку країни. Розроблена система взаємодії соціокультурних чинників у соціальній ринковій економіці. Показано, що соціальна економіка передбачає високий рівень розвитку цих чинників, а люди, що їх реалізують, повинні мати високу духовну розвиненість, культуру та бути професіоналами своєї справи, здібними неперевно навчатись та удосконалюватись. The purpose of this work is an analysis of the systems of basic component factors of influence on the social market economy of country with determination of them high-quality descriptions. Adduction results of analysis of basic component factors of influence on the socially oriented market economy of country. The developed system of co-operation of sociokurtumikh factors is in a social market economy. It is rotined that a social economy foresees the high level of development of these factors, and people, that they will be realized, must have high spiritual developed, culture and to be the business professionals, capable continuously to study and perfected. In society it must not be institucional'nikh factors, inherent economic to the backward countries. The state, public organizations and political parties, must have the proper strategic vector of development of country. It follows to send subsequent researches in the direction of exposure of reasons of braking of passing to the social economy in Ukraine.
Analysis of basic component factors of influence on the social market economy of country
Keywords: соціокультурні чинники; соціальна економіка; духовна розвиненість; культура; sociokul'turni factors; social economy; spiritual developed; culture